(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The most prevalent metabolic illness, diabetic mellitus (DM), is caused by a problem with insulin production. DM promotes the gradual degeneration of pancreatic cells, which raises blood sugar levels. Around 2.1 trillion dollars are invested in global health industries by diabetic wound repair therapies. This is a result of the difficulties that skin ulcers offer in the wound healing process, such as a shortage of macrophage and fibroblast growth factors (TGF-b1 and PDGF, respectively), all of which are required for the production of extracellular matrix (ECM). Nanofibers have been created by electrospinning with large porosity, excellent humidity absorption, a superior oxygen exchange rate, and certain antibacterial properties in response to the growth of medicinal materials and pharmaceutical technology. By including bioactive substances (such growth factors, genes, proteins/peptides, stem cells/exosomes, etc.) and nonbioactive materials, these nanoparticles/hydrogels aid in the healing of diabetic wounds (metal ions, oxygen, nitric oxide, etc.) Due to the slow wound healing process, wound care is a significant biomedical topic that presents difficulties. Malnutrition, insufficient oxygen, smoking, illnesses (such as diabetes and cancer), microbial infections, and other conditions are some of the causes of sluggish wound healing. Currently utilized wound dressings have a number of drawbacks, such as inadequate antibacterial action. Thus, we aimed to go into further depth about the NF (nanofiber) system's aforementioned characteristics for DM complications.